Respuestas

  • Usuario de Brainly
2013-11-14T20:56:25+01:00
**( \sqrt{2}-3)( \sqrt{2}+5) = \sqrt{2}^{2} +5 \sqrt{2}- 3\sqrt{2}-15 =

 2-15+5 \sqrt{2}-3 \sqrt{2} = -13+2 \sqrt{2} =

2 \sqrt{2}=13  ===> 4*2 = 169  ===> 8 \neq 169


**2 \sqrt{5} *( \sqrt{10}-3 \sqrt{20}) = 2 \sqrt{5*10} - ((2*3)*( \sqrt{5*20})) =

2 \sqrt{50}=6 \sqrt{100}  ===> 2 \sqrt{50} = 6*10 ===>

(2 \sqrt{50} )^{2} = 60^2 ===> 4*50=3600  ===> 200 \neq 3600


** \sqrt[4]{5} =  \sqrt[4*3]{5^3} =  \sqrt[12]{125}
  
 \sqrt[4]{7} = \sqrt[4*3]{7^3} =  \sqrt[12]{343}

 \sqrt[6]{11} = \sqrt[6*2]{11^2} = \sqrt[12]{121}

El menor es  \sqrt[12]{121} , luego está  \sqrt[12]{125} , y el mayor es  \sqrt[12]{343}

espero que te sirva
saludos